Pengaruh Religiusitas, Pelayanan Islami, Kepuasan Kerja terhadap Loyalitas Karyawan PTS di Jawa Tengah - Mukaramah, Maya; Sholahuddin, Muhammad (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to analyze the influence of religiosity and islamic service quality on employee loyalty with job safisfaction as a mediating variable at the muhammadiyah university of surakarta. Methodology: research uses quantitative methods with a survey approach. The sample consisted of 150 empliyees selected randomly. Data was collected through questionnaires and analyzed using structural equation modeling SEM based on Smart PLS. Results: Religiosity and Islamic service quality were proven to have a positive and significant effect on employee loyalty and job satisfaction. Job satisfaction also significantly mediates the influence of religiosity and Islamic service quality on employee loyalty. Conclusions: This study concluded that religiosity and Islamic service quality have a positive and significant effect on employee loyalty at Universitas Muhammadiyah Surakarta. Job satisfaction is also proven to mediate the relationship between religiosity and Islamic service quality to employee loyalty. This means that the higher the value of religiosity and Islamic service quality applied, the higher the employee satisfaction and loyalty to the institution. Limitations: This research is limited to one educational institution with a relatively small sample size, so generalization to other organizations requires caution. Contribution: This research contributes to the development of a human resource management model based on religious values ??and Islamic services in the context of higher education.